2022
DOI: 10.1037/emo0001060
|View full text |Cite
|
Sign up to set email alerts
|

Prospective associations between emotion regulation and depressive symptoms among Mexican-origin adolescents.

Abstract: Reappraisal (reconstruing emotional experiences to alter their impact) and suppression (inhibiting emotionally expressive behavior) are emotion-regulation strategies with important implications for depression. While reappraisal generally predicts lower depressive symptoms, suppression generally predicts higher depressive symptoms. Because cultural factors can influence the processes involved in these links and because adolescence-especially for ethnic minority youth-brings particular emotional challenges, it's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 70 publications
2
8
0
Order By: Relevance
“…At the same time, both adaptive and maladaptive strategies displayed similar levels of associations with the absence of anhedonia. These findings are aligned with the results of earlier research on anhedonia (Nelis et al, 2015;Werner-Seidler et al, 2013;Young et al, 2022), and they are in agreement with other studies that have more broadly analyzed the relationship between emotional regulation and wellbeing (Kraiss et al, 2020). Anhedonia is one of the defining elements of depression, and it has been tied to worse prognoses for the disorder (Riskind et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, both adaptive and maladaptive strategies displayed similar levels of associations with the absence of anhedonia. These findings are aligned with the results of earlier research on anhedonia (Nelis et al, 2015;Werner-Seidler et al, 2013;Young et al, 2022), and they are in agreement with other studies that have more broadly analyzed the relationship between emotional regulation and wellbeing (Kraiss et al, 2020). Anhedonia is one of the defining elements of depression, and it has been tied to worse prognoses for the disorder (Riskind et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…There has been little research to date focusing specifically on the associations between the various emotional regulation strategies and anhedonia (Raes, 2014). One recent study by Young et al (2022) that did look at this topic found that the habitual use of cognitive reappraisal strategy was significantly associated with lower rates of anhedonia over a period of three years in a sample of adolescents. Meanwhile, greater levels of anhedonia have been tied to less frequent use of strategies aimed at regulating and promoting the appearance of positive emotions (Nelis et al, 2015;Werner-Seidler et al, 2013).…”
Section: Emotional Regulation Strategies and Anhedoniamentioning
confidence: 99%
“…For example, a meta-analysis supports that expressive suppression may have a detrimental effect on resilience in individuals with Western cultural values but no effect on resilience in individuals with Eastern cultural values (Hu et al 2014). Similarly, a prospective study in a sample of Mexican-origin adolescents found the suppression of negative emotion (but not positive emotion) predicted decreases in anhedonia symptoms of depression (Young et al 2022). One explanation for these findings is that collectivistic-oriented cultures (e.g., Asian and Mexican), compared with more individualisticoriented cultures (e.g., European), place a higher value on expressive suppression especially of negative emotion, perhaps to support interpersonal harmony and social goals (Markus & Kitayama 1991, Mesquita 2001, Wilms et al 2020.…”
Section: 18mentioning
confidence: 97%
“…Second, an important future direction is to study whether the findings from the present study generalize to other immigrant or cultural samples. For example, some research has found that suppression of positive emotions is negatively associated with psychological health in Mexican Americans, but not Chinese Americans in the United States (Su et al., 2015; Young et al., 2021). Furthermore, our findings may not generalize to Chinese adolescents in China due to the unique experience of immigration and the cultural adjustments that come with it.…”
Section: Discussionmentioning
confidence: 99%